A RESEARCH ON ORGANIZATIONAL IDENTITY AND ORGANIZATIONAL CITIZENSHIP RELATIONS IN SYMBIOTIC COLLABORATIONS - Akduru, Hale Eda (Bursa Teknik Üniversitesi, 2022)
Symbiotic collaborations, as a common type of collaborations between businesses, are based on the establishment of a common life shaped within the framework of trust and common purpose. The purpose of the symbiotic relationship is to survive by providing mutual benefits and to face environmental hazards together. The aim of this study is to examine the relationship between organizational identity perceptions of employees and organizational citizenship behavior tendencies in symbiotic organization structures. And the data is obtained from a sample of 116 people working in a recycling company and a textile company that have a symbiotic relationship in Uşak Organized Industrial Zone. According to the research findings, while gender, age, education level and marital status variables do not affect the organizational citizenship behavior tendencies of employees in symbiotic organizations, wage and working years variables do. In addition, there is a positive correlation at the level of significance between the organizational identity perceptions of employees in symbiotic organizations and their organizational citizenship behavior tendencies. In this context, various suggestions have been made to increase the organizational identity perceptions of employees in symbiotic organizations.

İşletmeler arası işbirliklerinden simbiyotik işbirlikleri güven ve ortak amaç çerçevesinde şekillenen ortak bir yaşam kurulması esasına dayanır. Simbiyotik ilişkide amaç işletmelerin karşılıklı çeşitli faydalar sağlayarak hayatta kalması ve çevresel tehlikelere karşı birlikte hareket etmesidir. Bu çalışmada simbiyotik örgütler yapılanmalarında çalışanların örgütsel kimlik algıları ile örgütsel vatandaşlık davranışı eğilimleri arasındaki ilişkiyi incelemek amaçlanmıştır. Nicel araştırma yöntemlerinden anket tekniği uygulanarak gerçekleştirilen çalışma için, Uşak Organize Sanayi Bölgesinde faaliyetini sürdüren ve simbiyotik ilişki içerisinde bulunan firmalardan bir geri dönüşüm işletmesi ve ona kaynak sağlayan bir tekstil firmasında çalışan toplam 116 kişilik örneklemden elde edilen veriler analizlere tabi tutulmuştur. Araştırma bulgularına göre simbiyotik örgütlerde çalışanların örgütsel vatandaşlık davranışı eğilimlerini cinsiyet, yaş, eğitim düzeyi ve medeni durum etkilemezken ücret düzeyi ve hizmet süresi etkilemektedir. Ayrıca çalışanların örgütsel kimlik algıları ile örgütsel vatandaşlık davranışı eğilimleri arasında anlamlılık düzeyinde pozitif yönlü bir ilişki bulunmaktadır. Bu bağlamda simbiyotik örgütlerde çalışanların örgütsel kimlik algılarını artırmaya yönelik çeşitli öneriler getirilmiştir.
SİMBİYOTİK İŞBİRLİKLERİNDE ÖRGÜTSEL KİMLİK İLE ÖRGÜTSEL VATANDAŞLIK İLİŞKİLERİ ÜZERİNE BİR ARAŞTIRMA